2016
DOI: 10.1002/rrq.163
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Research on Vocabulary Instruction That Impacts Text Comprehension

Abstract: Although numerous studies have identified a correlational relationship between vocabulary and comprehension, we know less about vocabulary interventions that impact reading comprehension. Therefore, this study is a systematic review of vocabulary interventions with comprehension outcomes. Analyses of 36 studies that met criteria are organized around (a) type of comprehension measure (i.e., comprehension of passages that included taught words or more generalized comprehension measures) and (b) type of intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
143
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(158 citation statements)
references
References 80 publications
(165 reference statements)
10
143
0
5
Order By: Relevance
“…Findings of four studies of these programs, shown in Table , found a mean effect size of 0.06 (n.s. ), corresponding to the outcomes on general comprehension reported by Wright and Cervetti (). For example, Academic Language Instruction for All Students is a vocabulary intervention designed to be used in regular English language arts classrooms with many language‐minority students.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Findings of four studies of these programs, shown in Table , found a mean effect size of 0.06 (n.s. ), corresponding to the outcomes on general comprehension reported by Wright and Cervetti (). For example, Academic Language Instruction for All Students is a vocabulary intervention designed to be used in regular English language arts classrooms with many language‐minority students.…”
Section: Resultssupporting
confidence: 66%
“…Vocabulary proficiency has been shown to have a relation with reading proficiency (Oslund, Clemens, Simmons, & Simmons, ; Uccelli, Phillips Galloway, Barr, Meneses, & Dobbs, ). In their review of research on vocabulary interventions in grades K–12, Wright and Cervetti () found positive effects on comprehension of passages containing specifically taught words but not on generalized comprehension.…”
Section: Methodsmentioning
confidence: 99%
“…The WLS program included robust instruction that extended over 15 weeks. The program is also consistent with Wright and Cervetti's () observation that teaching students to use multiple strategies flexibly is a more promising approach than simply teaching one or two strategies. All in all, the instructional approach used in our program builds on previous research by using robust instruction over a substantial period of time to teach students to use multiple strategies and to use them flexibly.…”
Section: Previous Research On Teaching Word‐learning Strategiessupporting
confidence: 80%
“…Such strong relationships raise the question of whether vocabulary instruction, particularly interventions, that use data on students' knowledge of the core vocabulary could influence comprehension performances. To date, vocabulary interventions have been surprisingly ineffective in changing student performances on generalized comprehension measures [89]. One explanation is that interventions have typically not focused on the words most prominent in the lexicon at different developmental levels.…”
Section: Limitations and Future Researchmentioning
confidence: 99%